Six Sigma to Reduce Claims Processing Errors in a Healthcare Payer Firm - Sunder M, Vijaya; Kunnath, Nidhin R. (Taylor and Francis, 2020)
As a continuous improvement practice, Six Sigma has been accepted globally across the service industry. In the past one decade, the application and success of Six Sigma in healthcare services has been remarkable. Despite the fact that several papers on Six Sigma have appeared in the erstwhile literature related to healthcare operations, there is a dearth of field studies highlighting the application of Six Sigma in healthcare outsourced firms, in specific to healthcare payers that engage in a non-clinical setup. The aim of this paper is to explore the role of Six Sigma within the healthcare payer outsourced firms, where error-free delivery becomes critical. The article contributes to the literature of Six Sigma in healthcare outsourcing highlighting how “Six Sigma as a methodology” could help reduce claims adjudication errors in a healthcare payer firm. The Six Sigma DMAIC project case study presented as part of the paper delivered a saving of USD 0.53 million and is a classic example of how Six Sigma can bring bottom-line impact to healthcare outsourced organizations. Managerial implications and lessons learned are discussed alongside the concluding notes.